2019
DOI: 10.1177/1049909119890556
|View full text |Cite
|
Sign up to set email alerts
|

Managing Opioids, Including Misuse and Addiction, in Patients With Serious Illness in Ambulatory Palliative Care: A Qualitative Study

Abstract: Background: Pain and opioid management are core ambulatory palliative care skills. Existing literature on how to manage opioid misuse/use disorder excludes patients found in palliative care settings, such as individuals with serious illness or those at the end of life. Objectives: We conducted an exploratory study to: (1) Identify the challenges palliative care clinicians face when prescribing opioids in ambulatory settings and (2) explore factors that affect opioid decision-making. Methods: We recruited palli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 20 publications
0
20
0
1
Order By: Relevance
“…Participants’ emphasis on the goal of comfort care as a justification for liberally prescribing opioids towards the end of life should also be interpreted within the context of research suggesting that doctors sometimes overestimate patients’ desire to be pain free at the expense of mental clarity 70. GPs in our study also seemed to have lower levels of concern regarding addiction and misuse in the palliative context than has been reported for palliative care physicians 71…”
Section: Discussionmentioning
confidence: 57%
“…Participants’ emphasis on the goal of comfort care as a justification for liberally prescribing opioids towards the end of life should also be interpreted within the context of research suggesting that doctors sometimes overestimate patients’ desire to be pain free at the expense of mental clarity 70. GPs in our study also seemed to have lower levels of concern regarding addiction and misuse in the palliative context than has been reported for palliative care physicians 71…”
Section: Discussionmentioning
confidence: 57%
“…HCP/VE stated that they need more specific education and a mobile team for both consultation and care provision tailored to the patient's needs. Recent research shows similar results [49][50][51][52]. The resources to provide optimal palliative care for patients with SUD+ appear insufficient.…”
Section: Discussionmentioning
confidence: 66%
“…Our team previously conducted two studies that provided insight into how to design cases and responses (clinical management strategies). 16 17 In a recent qualitative study, we asked palliative care clinicians to describe challenges they face when caring for patients with serious illness prescribed opioid therapy. Clinical management challenges identified included managing opioids in patients with a history of substance use disorders and addressing opioid-related harms, including misuse behaviours such as concurrent use of cocaine or medications that were not prescribed such as benzodiazepines.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Clinical management challenges identified included managing opioids in patients with a history of substance use disorders and addressing opioid-related harms, including misuse behaviours such as concurrent use of cocaine or medications that were not prescribed such as benzodiazepines. 16 In addition to substance use, other prior work has identified several common and challenging misuse behaviours that may arise in patients prescribed opioid therapy such as taking more opioids than prescribed or aggressive behaviour. 17 Importantly, our qualitative study consistently identified prognosis for life expectancy (referred to in this article as prognosis) as an important factor that influences opioid decision-making in individuals with serious illness.…”
Section: Methods and Analysismentioning
confidence: 99%